"As Crônicas de gelo e fogo", narrativas transmidiáticas e a leitura como ato responsivo - Vieira, Marília Daniele Soares (2017)
The present research has as objective to defend the place of the Midia Literacy among the educational (multi)literacies, above all on what refers to the use of transmidia narratives as objects of the learning to read process, seeking consider about how such practices can collaborate to the critic and reading formation of the students. Therefore, the adopted corpus was constituted by a group of interviews made with participants of the grassroots movements of 2013 — which are know as “The Vinegar Revolt” — that protested in numerous ways, including the use of signs that contained words of protest and chants in general. For our investigation, interested us, however, to observe those that demonstrated a particular kind of diaology: the appropriation of speeches from the transmidia universe (JENKINS, 2009), of the A Song of Ice And Fire (2010-2012), from the author George R. R. Martin, in their signs. With this, our objective was to comprehend how the reading of the mentioned transmidia universe, and many others similars to it, can collaborate to the formation of the critic reader. For the theoretical elaboration of this research, we founded ourselves in Bakhtin and The Circle’s dialogic theory of language, specially in the concepts of dialogic relationships and active and creative comprehension, allying to the readings about literacy (SOARES, 2009), multiliteracies (ROJO, 2009; STREET, 2014) and critic literacy (CASSANY, 2005; PAES DE BARROS, 2005, 2009, 2012). Such conjectures allied themselves to the concepts of Convergence Culture and Midia Literacy proposed by Henry Jenkins (2009). The data analysis reveled that the participants subjects of this research did various literacy practices in out-of-school contexts, in the other hand, the ones perceived insides the school context were yet very limited and made little contributions to the development of literacies demanded by other social spheres. It was observed, in that manner, that the dialogical interactions provided by the convergence culture and by the transmidia model of content production has been each time more relevant to the process of reading as active comprehension. However, such literacy practice not only has not been integrated to the educational sphere, as it tends to be pushed back by the voices of authority in such sphere.